A New MSB Modular multiplication Algorithm and its Implementation using 4-2 Compressor (University of Khartoum Engineering Journal, 2022)
Currently, enhancing the performance of modular multiplication is very important for high performancemicroprocessors. Multiplication is inherently a slow operation as a large number of partial products. In this paper,Implementation of MSB modular multiplication using 4-2 compressor using the last two most significant bits isintroduced. Using the two most significant bits (MSB's) for reduction in this technique, we will avoid the use ofthe carrier so, no carry store. However, we don’t need to use the feedback which used in MontgomeryMultiplication [13]. The total power-efficiency (power-delay-product) is reduced using low-power low-voltage 4-2compressors. The circuits implemented using Matlab simulation.